Pengaruh Financial Distress, Inflasi, dan Nilai Tukar Terhadap Keputusan Investasi serta Implikasinya Pada Nilai Perusahaan - Taufik Hidayat; Adibah Yahya; Maulina Dyah Permatasari (LPPM Universitas Pelita Bangsa, 2023)
The purpose of this study is to analyze the effect of financial distress, inflation, exchange rates on investment decisions and their implications for firm value. The value of the company shows the company's performance seen from the demand and supply of stock prices. During the Covid-19 pandemic, stock prices experienced a sharp decline, thus affecting the value of the company. This condition can have an impact on financial distress, where when there is financial distress the value of the company will decrease. The high inflation rate has an impact on the decline in the value of the company as a result of the decreasing level of investor confidence in investing their capital. This can be used as a signal for the company's management in making investment decisions in order to increase the value of the company. The population in this study is the property and real estate sub-sector companies listed on the Indonesian stock exchange for the 2019-2021 period, which are 83 companies. The sampling technique used was purposive sampling. The tests used in this study were descriptive statistical tests, classical assumption tests (normality, multicollinearity, heteroscedasticity and autocorrelation) and hypothesis testing (correlation & determination coefficient tests, t-test, and F-test). The results showed that financial distress had a negative effect on firm value, inflation had a positive effect on firm value, and the exchange rate had no effect on firm value. Investment decision variables have no effect on firm value.